Research on simplified modeling of large-scale wind farms based on equivalent transfer function and aggregate equivalent - Ding, Ran; Yang, Chun; Mei, Rui; Yang, Hongyu; Ji, Jie; Shi, Qi (Frontiers in Energy Research, 2023)
In the grid-connected large-scale wind farms, because of the large number of wind turbines, there are many problems in the control research based on the traditional detailed model of wind turbines, such as long simulation time and high model order, etc. , in order to realize the fast simulation and grid-connected transient research of wind farm under various operating conditions, a simplified wind turbine model based on equivalent transfer function and an aggregate equivalent model based on large-scale wind farm connection structure are proposed in this paper. Firstly, the general detailed mathematical model of the existing wind turbine is analyzed and a reasonable simplification strategy is designed. Based on this, the simplified model is built according to the equivalent transfer function, and the electrical interface connecting with the power grid is established. Then the connection mode of the collecting system of the wind farm is analyzed, the equivalent line loss model of the collecting line is considered, the simplified wind turbines are classified and aggregated, and the converged fans are calculated by the improved capacity weighting method, the grid-connected simplified modeling of large-scale wind farm is realized. Finally, a model of the wind power flexible DC grid-connected system for wind farm and MMC-HVDC is built. The effectiveness of the proposed model is verified by simulation analysis under typical operating conditions.